Collaborative Management Between School Principals and Parents in Supporting the Learning of Students with Special Needs at Tenggarong Public Elementary School 035 - Hamidah Hamidah; Usfandi Haryaka; Sudarman Sudarman; Lambang Subagiyo; Widyatmike Gede Mulawarman; Nurlaili Nurlaili (Journal of Educational Sciences, 2026)
Inclusive education requires effective collaboration between schools and families to support the development of students with special needs. This study aims to analyze the collaborative management between the principal and parents in supporting the learning of students with special needs at SD Negeri 035 Tenggarong. The study employed a qualitative descriptive approach with a case study design. Data were collected through interviews, observations, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results showed that the functions of Planning, Organizing, Implementing, and Monitoring the collaboration had been carried out quite well through intensive communication, role sharing, parental involvement, and regular monitoring of student progress. Supporting factors included communication, school cooperation, parental involvement, and school program support. Hindering factors included parents’ time constraints, differing understandings of students’ needs, limited facilities, and the lack of a formally established inclusion team. Collaboration has a positive impact on students’ academic and social development, as well as their self-confidence. The novelty of this study lies in its integrated assessment of collaboration management between school principals and parents through management functions to support the learning of students with special needs. The study concludes that collaboration management has been implemented quite effectively and supports the implementation of inclusive education.